Aquisição nasal de Staphylococcus aureus por recém-nascidos saudáveis - Cardoso, Marcelle Paiano (2007)
A significant percentile of the adult population bears Staphylococcus aureus in the nasal vestibules, skin and mucous membranes, but in newborns that percentage is outstanding, once it reaches 100% in the four-day-old newborns. In the present study both, the acquisition of nasal Staphylococcus aureus among 50 healthy newborns and the occurrence of the microorganism in their respective mothers' mammal areola/nipples was investigated. Three samples from the nasal vestibules and one from the areola/nipples were collected. The biological material was sown into salty mannitol agar and later it was maintained into trypticasein soy broth for 24 hours for proceeding a new sowing. Staphylococcus aureus samples were assayed to observe the susceptibility to oxacillin, by using a technique known as 'determination of minimum inhibitory concentration'. Thus the resistant oxacillin were analyzed in relation to both, susceptibility to other antimicrobial - by using the disk diffusion method - and the presence of mecA gene. Results showed that, among parturients, 56% (28/50) showed positive culture for Staphylococcus aureus, whereas among the newborns, 90% (45/50) provided the isolation of the microorganism. In relation to the binomial mother-son, 50% (25/50) of the pairs carried the microorganism. Approximately 59% (43/73) of the samples were isolated from direct sowing, having an increment of 51% when the swab was maintained in enrichment medium. The resistance to oxacillin, through the test of minimum inhibitory concentration, was detected in 7 out of the 73 samples, and,when using the disk diffusion method, the result was confirmed in 6 of them. The sensibility to linezolide, vancomycin, mupyrocin and telithromycin was of 100%, whereas the resistance to cefoxitin was of 100%. In relation to the detection of mecA gene, results showed that 85.7% (6) of the resistant samples to oxacillin carried that gene.